Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2001
DOI: 10.1115/2001-gt-0345
|View full text |Cite
|
Sign up to set email alerts
|

3D Transonic Flow in a Compressor Cascade With Shock-Induced Corner Stall

Abstract: An experimental and numerical study of the transonic flow through a linear compressor cascade with endwalls was conducted. The cascade with a low aspect ratio of 1.34 was tested at an inlet Mach number of 1.09 and a Reynolds number of 1.9×106. Detailed flow visualizations on the surfaces and 5-hole probe measurements inside the blading and in the wake region showed clearly a 3-dimensional boundary layer separation on the blade surface and the sidewall, and a severe corner stall induced by a strong 3D shock sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…A theory giving expected spanwise wavelengths for a circular cylinder was developed by Kestin and Wood 9 in 1970. "Streaky structures" and streamwise vortices have been observed and predicted on flat plates 10 , on compressor blades 11,12 and on the convex surface of a supercritical airfoil, following an initial concave surface exhibiting Görtler vorticity 13 . In a study of plane shear layers, Lasheras et al 14 have concluded that these are unstable to three-dimensional perturbations in the upstream conditions.…”
Section: Introductionmentioning
confidence: 97%
“…A theory giving expected spanwise wavelengths for a circular cylinder was developed by Kestin and Wood 9 in 1970. "Streaky structures" and streamwise vortices have been observed and predicted on flat plates 10 , on compressor blades 11,12 and on the convex surface of a supercritical airfoil, following an initial concave surface exhibiting Görtler vorticity 13 . In a study of plane shear layers, Lasheras et al 14 have concluded that these are unstable to three-dimensional perturbations in the upstream conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Through the years, to improve the work performance of highly loaded axial compressor, the structure of corner separation has been studied worldly in the aeronautical research field. [1][2][3][4][5][6][7][8][9][10][11] Compressor cascade is a simplified model of real axial compressor stator blade and has been widely applied to researching the mechanism and control of corner separation, as well as the compressor tip clearance flow structures and effects of threedimensional compressor blades. 12,13 Active flow control methods, such as boundary layer suction, [14][15][16] flow blowing, 17,18 plasma flow control 19,21 etc, have been applied to the control of compressor cascade corner separations over years.…”
Section: Introductionmentioning
confidence: 99%
“…To control the corner separation effectively, the design of both active and passive methods should be based on the in-depth understanding of flow structures in the compressor cascade flow passage and various efforts have been spared. [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In low speed flow, with inlet Mach number under 0.3, detailed researches on the flow structures in the compressor cascade flow passage have been launched. 3,[7][8][9][10] When inlet Mach number increases to be bigger than 0.3, the flow becomes more unsteady and compressible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have revealed streamwise vortices and "streaky structures" on flat plates 1 and on the suction surface of compressor blades 2,3 . Turbine blade designers are quite familiar with the phenomenon of Görtler vorticity; this is thought to occur predominantly on the concave pressure surfaces of turbine blades.…”
Section: Introductionmentioning
confidence: 99%